ARTROPODOFAUNA ASOCIADA A GEASTRUM TRIPLEX JUNGH GASTEROMYCETES , BASIDIOMYCOTINA ) . V REGIÓN , CHILE (Acta Entomológica Chilena, 2022)
The purpose of the present paper is to survey the insects -Geastrum triplex relationships during thefruiting period of fungus.The study was carried out in the Reserva Forestal Peñuelas, V Región, under mediterranean chínate,between 06-01-1996 and 08-17-1996.Members of 23 species, distributed in 11 taxa of arthropods, were collected from fructifications ofGeastrum triplex'. 13 mycetoxenes, 6 mycetophilous and 4 mycetobionts. Eleven out of twenty three specieswere found only in fructifications. The most abundant taxa were Collembola and Coleóptera, as well as inthe area of study.The main conclusions are: a) Peñuelas is a new record for Geastrum triplex in Chile, b) biological aspectsof development of principal mycetobionts, Caenocara humeralis White (Anobiidae) and Metophalmoidescastrii Dajoz (Lathridiidae), are described, c) Geastrum triplex is recorded for first time as host of C.humeralis and M. castrii, d) a positive correlation between dammage of the gleba and the number of insectsis established.
Keywords: Geastrum triplex, arthropods, fruiting period, Chile